(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the short-term functional and radiological results in patients with Developmental Dysplasia of Hip (DDH) operated through a modified medial approach using two intervals. Methods: This descriptive study was conducted in Paediatric Orthopedic Unit Children’s Hospital and Institute of Child Health Lahore from 10th August 2019 to 10th August 2021.All children of DDH with age 18 months or less fulfilling the inclusion criteria were operated through modified medial approach using two intervals. Post operative functional results were assessed with McKay criteria and graded as excellent, good,fair and poor. Radiographic evaluation was done with Severin’s classification. Avascular necrosis(AVN) was classified using Kalamchi and MacEwen classification. Results: In this study 21 patients were included. The Mean age at the time of primary surgery was 12.5 ± 2.9 months, Females were 14 (66.66%) and males were 7( 33.33%). Mean Post operative follow-up period was 16.7 ± 3.3 months. Excellent functional outcome was noted in 17(80.95%) and good in 4(19.04%) as per McKay’s criteria. Radiographically 17(80.95%) patients had Severin’s Class I, 3(14.28%) had Class II and 1(4.76%) patient had Severin’s Class III outcome. We noted that 1(4.76% ) patient developed AVN(Kalamchi and MacEwen group II) Conclusion: Excellent and good short term functional and radiological results were achieved in DDH patients treated with modified medial approach using two intervals.